IOEASMA: an integrated clinical and educational pathway for managing asthma in children and adolescents - Sebastiano Guarnaccia; Gaia Pecorelli; Marina Bianchi; Massimo Cartabia; Gianluigi Casadei; Ada Pluda; Cristina Quecchia; Valeria Gretter; Maurizio Bonati (BMC, 2017)
Abstract Background Due to the lack of real life clinical and educational studies, "Io e l'Asma" Centre performed this implementation research (IR). Evaluate long-term effectiveness on bronchial asthma control of an integrated clinical and educational pathway for asthmatic children and adolescents. Methods An observational retrospective pre-post intervention IR study was conducted among 262 children with asthma, ages 6-15 yrs. The intervention protocol included three clinical visits 8 weeks apart; an educational course at visit 1, post intervention consisted in two follow-up visits 6 months apart. The primary outcome was to verify the percentage of children who achieved bronchial asthma control at each visit. Secondary outcomes were based on daily therapy modulation, hospital admissions and the number of school days missed. An economic assessment was also included. Results Two hundred sixty two children with bronchial asthma completed the pathway and were included in the analysis. The percentage of children who obtained disease control increased from 44% at visit 1 to 79% at visit 3 and at 1-year follow-up was 83%. Hospital admissions represent 11% of children: 8% before the intervention, 2% during the intervention, and 1% before and during the intervention; no hospitalizations related to bronchial asthma exacerbations were reported during the 2 follow-up visits. Conclusions The therapeutic-educational pathway was adapted according to the international guidelines and the primary performance indicators. Our findings confirmed that the clinical plus educational approach, shared between specialists and family physicians, is an effective template for asthma management. These findings also demonstrated a strong economic advantage.